Burkina Faso : Poverty Reduction Strategy Paper Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report, 2007)
This Joint Staff Advisory Note reviews the sixth annual progress report (APR) on the implementation of Burkina Faso's Poverty Reduction Strategy (PRS). The APR notes that poverty has been further reduced to an estimated 42 percent in 2005 from an estimated 54 percent in 1998. Poverty declined owing mostly to a reduction in the incidence of rural poverty. The APR also informs about progress made regarding access to basic services, employment opportunities for the poor, and improved governance.